The role of Enterococcus faecalis during co-infection with avian pathogenic Escherichia coli in avian colibacillosis. Issue 6 (1st November 2020) - Walker, Grayson K.; Suyemoto, M. Mitsu; Gall, Sesny; Chen, Laura; Thakur, Siddhartha; Borst, Luke B.
ABSTRACT: Enterococcus spp. (ENT) are frequently co-isolated with avian pathogenic E. coli (APEC) from poultry with colibacillosis, a leading cause of flock mortality. Although largely overlooked, ENT may play an active role in these infections. To assess the frequency of ENT co-isolation in colibacillosis, cultures were collected from birds with gross lesions of omphalitis, polyserositis, and septicaemia over a 3-year period from three turkey flocks and three broiler flocks. In birds diagnosed with colibacillosis based on gross findings and isolation of E. coli, ENT were co-isolated with APEC in 35.7% ( n  = 41/115) of colibacillosis mortality and 3.7% of total mortality ( n  = 41/1122). Co-isolated APEC and ENT pairs ( n  = 41) were further characterized using antimicrobial resistance phenotyping and in vitro co-culture assays. E. faecalis (EF) was the most commonly co-isolated species (68% n  = 28/41) and tetracycline resistance was the resistance phenotype most commonly found among APEC (51% n  = 21/41) and ENT (93% n  = 38/41). Under iron-restricted conditions, EF enhanced APEC growth in a proximity-dependent manner and APEC grown in mixed culture with EF exhibited a significant growth and survival advantage ( P  ≤ 0.01). In an embryo lethality assay, APEC co-infection with EF resulted in decreased survival of broiler embryos compared to mono-infections ( P  ≤ 0.05). These data demonstrate that EF augmented APEC survival and growth under iron limiting conditions, possibly translating to the increased virulence of APEC in broiler embryos. Thus, ENT co-infections may be a previously unrecognized contributor to colibacillosis-related mortality. Further investigations into the mechanism of this interaction are warranted. RESEARCH HIGHLIGHTS Enterococcus is frequently co-isolated with avian pathogenic E. coli (APEC). Enterococcus faecalis (EF) enhances survival of APEC in iron restricted conditions. EF co-infection increases APEC virulence in broiler embryos.